Reversal Treatment in Oral Anticoagulant-Related Intracerebral Hemorrhage—An Observational Study Based on the Swedish Stroke Register - Apostolaki-Hansson, Trine; Ullberg, Teresa; Pihlsgård, Mats; Norrving, Bo; Petersson, Jesper (Frontiers in Neurology, 2020)
Introduction: Intracerebral hemorrhage (ICH) is the most serious adverse effect of oral anticoagulant (OAC) treatment. The effect of OAC reversal therapy on outcome is uncertain. We compared 90-day survival and functional outcome in patients with OAC-ICH who received OAC reversal therapy with those who did not. Methods: Data from The Swedish Stroke Register (Riksstroke) for all registered cases of OAC-ICH during 2017 (572 patients) were used to obtain information on reversal (n=369) and non-reversal (n=203) treatment receiving patients. Univariate and multivariate Cox regression analysis stratified for level of consciousness (LOC) on admission, and adjustment for relevant baseline variables, was used to compare 90-day Hazard Ratios (HR) for mortality. Results: Sixty-five percent of patients received reversal treatment. These patients were younger, more often pre-stroke independent and alert at presentation. Withholding reversal treatment was associated with an increased death rate (HR = 1.47; 95% CI: 1.08 – 2.01) in a Cox regression model stratified for LOC and adjusted for baseline imbalances. Additional factors associated with an increased 90-day death rate were male sex (HR = 1.42; 95% CI: 1.06 – 1.92), age (HR = 1.05; 95% CI: 1.02 – 1.07), and intraventricular hemorrhage (HR = 2.41; CI: 1.77 – 3.29). Conclusion: In this large observational study 35% of patients with OAC-ICH did not receive reversal treatment. Patients receiving OAC-reversal treatment had an improved 90-day mortality outcome compared to those not receiving treatment. Mortality was strongly related to LOC. Further, and larger, studies are required to determine which patient groups may benefit from reversal therapy and in whom non-reversal is adequate.